A Retro‐biosynthesis‐Based Route to Generate Pinene‐Derived Polyesters. (21st May 2019) - Stamm, Arne; Biundo, Antonino; Schmidt, Björn; Brücher, Jörg; Lundmark, Stefan; Olsén, Peter; Fogelström, Linda; Malmström, Eva; Bornscheuer, Uwe T.; Syrén, Per‐Olof
Abstract: Significantly increased production of biobased polymers is a prerequisite to replace petroleum‐based materials towards reaching a circular bioeconomy. However, many renewable building blocks from wood and other plant material are not directly amenable for polymerization, due to their inert backbones and/or lack of functional group compatibility with the desired polymerization type. Based on a retro‐biosynthetic analysis of polyesters, a chemoenzymatic route from (−)‐α‐pinene towards a verbanone‐based lactone, which is further used in ring‐opening polymerization, is presented. Generated pinene‐derived polyesters showed elevated degradation and glass transition temperatures, compared with poly(ϵ‐decalactone), which lacks a ring structure in its backbone. Semirational enzyme engineering of the cyclohexanone monooxygenase from Acinetobacter calcoaceticus enabled the biosynthesis of the key lactone intermediate for the targeted polyester. As a proof of principle, one enzyme variant identified from screening in a microtiter plate was used in biocatalytic upscaling, which afforded the bicyclic lactone in 39 % conversion in shake flask scale reactions. Abstract : Breaking it down : A chemoenzymatic route from (−)‐α‐pinene towards a verbanone‐based lactone, which is further used in ring‐opening polymerization (ROP) to afford pinene‐derived polyesters with enhanced thermal properties, is proposed. The active site of A. calcoaceticus cyclohexanone monooxygenase is enlarged to allow the generation of the bulky (−)‐ cis ‐verbanone lactone intermediate.